2018
DOI: 10.3390/molecules23092174
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Bioavailability of Two Diosmin Formulations after Oral Administration to Healthy Volunteers

Abstract: Diosmin is a flavonoid commonly found in citrus fruits, largely used as adjuvant treatment for circulatory disorders, including chronic venous insufficiency (CVI) and hemorrhoids. Following oral administration, diosmin is not directly absorbed but must first be hydrolyzed into its aglycone, diosmetin, which is then absorbed into the systemic circulation. The aim of the current cross-over clinical study was to assess the pharmacokinetic profile of µSmin® Plus, a micronized diosmin flavonoid complex standardized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 18 publications
1
50
2
1
Order By: Relevance
“…Specifically, the inhibition of drug-biotransformation CYP 450 enzymes [49] influences metabolic and pharmacokinetic properties of themselves and other simultaneously administered drugs [50]. Literature data suggest that diosmin is poorly absorbed after oral administration and this affects all pharmacokinetic parameters, including bioavailability [51]. It has been also observed that plasma concentrations have improved slightly when diosmin was administered in a micronized form, as the smaller particle size provided an increased surface area available for intestinal absorption [52].…”
Section: Absorption Uptake and Pharmacokineticsmentioning
confidence: 99%
“…Specifically, the inhibition of drug-biotransformation CYP 450 enzymes [49] influences metabolic and pharmacokinetic properties of themselves and other simultaneously administered drugs [50]. Literature data suggest that diosmin is poorly absorbed after oral administration and this affects all pharmacokinetic parameters, including bioavailability [51]. It has been also observed that plasma concentrations have improved slightly when diosmin was administered in a micronized form, as the smaller particle size provided an increased surface area available for intestinal absorption [52].…”
Section: Absorption Uptake and Pharmacokineticsmentioning
confidence: 99%
“…Russo et al compared this with an unformulated micronized diosmin in 16 healthy volunteers. Their data indicate that lSminPlus was rapidly and well absorbed into systemic circulation (Russo et al 2018). At the same time, metabolic conversion must be considered when estimating the bioavailability and efficacy of flavonoids for pharmacological use.…”
Section: The Limitations Of Dietary Flavonoids In Clinical Applicationmentioning
confidence: 99%
“…Therefore, the enzyme specificity and distribution play a vital role in flavonoid absorption. In most cases, it is reported that in brush borders of intestine and absorption in the liver, flavonoids undergo phase II metabolism to form various glucuronides, sulfates or methylated derivatives (Koutsos et al, 2015;Russo et al, 2018;Scalbert and Williamson, 2000). The small intestine directly absorbs low-molecular-weight flavonoids; however, high-molecular-weight flavonoids reach the colon almost unchanged, and they are hydrolyzed by intense metabolic activity before absorption.…”
Section: Bioavailability Of Phenolic Compoundsmentioning
confidence: 99%